Prejudice Towards African American as Portrayed in Roll of Thunder, Hear My Cry Novel Written by Mildred D. Taylor - Santoso, Eko Prasetyo Budi; Ariani, Setya; Sudirman, Eka Pratiwi (Fakultas Ilmu Budaya Universitas Mulawarman, 2024)
This research aims to reveal the kinds of prejudice experienced by African Americans and to know the behaviors of African Americans when they experience prejudice. This research utilizes Gordon Allport’s acting out prejudice and traits of prejudice victimization theory. The data in this research are in the form of narration and dialogue. The result of this research shows that African-American characters in Roll of Thunder, Hear My Cry Novel experience three forms of prejudice, namely: antilocution, discrimination, and physical attack. Prejudice actions occur because white groups consider themselves as the majority and better than African American groups. The result also shows that there are extropunitive and intropunitive traits represented in The Roll of Thunder, Hear My Cry Novel, namely; (1) withdrawal and passivity, (2) strengthening in-group, (3) slyness and cunning, (4) prejudice against out-group, and (5) aggression and revolt.